IMPLEMENTASI SELEKSI TERBUKA JABATAN PIMPINAN TINGGI (JPT) PRATAMA BAGI PNS DALAM RANGKA REFORMASI BIROKRASI DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN SUMEDANG PROVINSI JAWA BARAT - Ismail, Ismail (Institut Pemerintahan Dalam Negeri, 2018)
Abstract Prior to the enactment of Law Number 5 of 2014 that concerning regulate State Civil Apparatus, filling in positions was not conducted openly, but rather featured superior privileges. After the birth of Law Number 5 Year 2014, open promotion has become one of the levers of the success of bureaucratic reform, this system is expected to prevent the politicization of bureaucracy, practicing of collusion, corruption and nepotism. Through open promotion, it will create a good system in the career of civil servants. Even though until now, it is imperative to carry out new open promotions at high leadership positions. The purpose of this study is to examine and analyze how the implementation process of open selection Pratama High Leadership Position for civil servants in the framework of bureaucratic reform in the Human Resources and Human Resources Development Agency of Sumedang Regency, West Java Province. The analytical tool in this study uses the implementation concept of George Edward III in Supriatna (2010: 175-176), there are 4 (four) variables in implementing a public policy, namely: “Communication, resources, disposition, and bureaucratic structure”. These four factors influence the success/failure of policy implementation. The research method is used qualitative research with descriptive methods and collecting data through observation and interview. The results of the research show that the implementation process has run quite well from the aspects of communication, aspects of resources, disposition aspects, and aspects of the bureaucratic structure but need to be maintained and improved again for the open selection process of the Pratama High Leadership Position in the framework of bureaucratic reform in Human Resources And Human Resources Agency Sumedang Regency, West Java Province. Keywords: implementation, open selection, pratama high leadership position, bureaucratic reform.